Evaluation of measles–rubella vaccination for mothers in early puerperal phase. Issue 9 (24th February 2016) - Hisano, Michi; Kato, Tatsuo; Inoue, Eisuke; Sago, Haruhiko; Yamaguchi, Koushi
Abstract: Background: The postpartum period is an ideal opportunity to vaccinate mothers with inadequate immunity to vaccine-preventable diseases including measles and rubella. Methods: A prospective study of measles–rubella (MR) vaccination in the early puerperal phase was conducted in 171 mothers, who had insufficient antibody titers when screened for immunity to measles (≤1:4 on the neutralization test [NT]) or rubella (≤1:16 on the hemagglutination inhibition [HI] test) during pregnancy. To evaluate the efficacy of MR vaccination in the postpartum period, we determined their post-vaccination antibody titers and immune responses to vaccination, and investigated the association between these and their prolactin (PRL) levels and Th1/Th2 ratios at the time of vaccination. We also examined the passage of viral RNA and antigen into breast milk. Results: Of the 169 participants who completed the study schedule, 117 and 101 had low antibody titers against measles and rubella, respectively. In the measles-seronegative group, the antibody-positive rate was 87% on the NT assay, and the NT geometric mean antibody titer was 11.4 (95% confidence interval [CI], 10.0–13.0). In the rubella-seronegative group, the antibody-positive rate was 88% on the HI test assay, and the HI geometric mean antibody titer was 64.0 (95% CI, 53.9–76.0). There was no association between the post-vaccination antibody titers and the PRL levels or Th1/Th2 ratios at the time of vaccination. In the rubella-seronegative group, subjects with higher Th1/Th2 ratios showed higher rates of responsiveness than those with lower ratios ( P  = 0.045). Although measles virus RNA was isolated from the breast milk of two vaccinated mothers, breastfeeding was not associated with clinical disease in any infants. Conclusion: MR vaccination in the early puerperal phase is considered an effective way to prevent the diseases, regardless of the mother's immunological status and hormonal milieu.